Pathogenic variability of Colletotrichum sublineolum isolates on sorghum differentials under greenhouse conditions in Jimma, Ethiopia. (14th December 2021) - Tsedaley, Binyam; Adugna, Girma; Lemessa, Fikre; Prom, Louis K.
Abstract: Sorghum anthracnose caused by Colletotrichum sublineolum is one of the most destructive diseases affecting sorghum production in Ethiopia. Pathogenic variability of C. sublineolum isolates on some sorghum differentials under greenhouse condition was evaluated in Jimma, Ethiopia. Highly significant ( P  < 0.001) differences among sorghum differentials, C. sublineolum isolates and their interactions on incubation period, aggressiveness, virulence index, virulence, the first and final anthracnose severity assessments, disease infection rate and AUDPC were studied. Among the interactions, the interaction between CsAs7 (isolate from Assosa zone field 7) and sorghum differentials had the shortest mean incubation period (3.5 days), highest first and final anthracnose severity, highest virulence index, fastest disease infection rate and highest AUDPC as compared to others. This isolate showed the most aggressive and virulent reaction than others followed by CsJm5. The interaction of PI570726 and SC748-5 sorghum differentials and all C. sublineolum isolates produce 100 and 80% resistant reactions, respectively and they could be used as good sources of resistance genes for breeding programs for sorghum anthracnose management.